The Role of Tuban Regency Social, Women's Empowerment and Child Protection and Community and Village Empowerment Service in Efforts to Handle Street Children in Tuban Regency - Humaidah, Isni; Kriswibowo, Arimurti (Borong Newinera Publisher, 2024)
The aim of this research is to find out and describe the role of Tuban Regency Social, Women's Empowerment and Child Protection and Community and Village Empowerment Service in efforts to handle street children in Tuban Regency. The research method used is qualitative research with a case study approach. Data collection techniques are interviews, observation and documentation. The technique for determining informants used was purposive and snowball techniques. The data analysis technique uses interactive data developed by Miles & Huberman, namely Data Collection, Data Condensation, Data Display, and Conclusions Drawing and Verifying. The results of research using role theory by Ife & Tesoriero (2008) are 1) Facilitating roles and skills are running well and the facilities provided in terms of facilities and infrastructure already exist 2) Educating roles and skills still have obstacles, namely the difficulty of changing mindsets from street children and in terms of this training is not going well because the number of street children who take part in training every year is still relatively small 3) Roles and Representation Skills have been carried out in collaboration with various parties 4) Roles and Technical Skills have gone well but still There is an obstacle, namely the lack of budget.